The - Dandelion, Pink (Oxford University Press, 2008)
In this generously illustrated book, Pink Dandelion, the leading expert on Quaker Studies, draws on the latest scholarship to chart the history of the sect and its present-day diversity around the world, exploring its unique approach to worship, belief, theology and language, and ecumenism. It concludes by placing the Quakers in the wider religious picture and predicting its future